The Role of Babu’ (Mother) among Blater in Madura - Yan Ariyani; Mery Atika; Wasis Purwo Wibowo; Sheily Herlyta Putri (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
This study aimed to reveal the role of Babu’ (Mother) in the lives of Blater in Madura, who is known as a tough, influential, and respected figure in society. Behind the masculine, fierce and polite image, Blater shows an attitude of respect, obedience, and glorification of the mother figure. This study uses a qualitative approach with a phenomenological design to explore the meaning of the Blater's life experiences towards the mother figure. Data collection techniques were carried out through in-depth interviews and documentation, with the main participants being five Blater in Bangkalan, Madura. The results of the study show that mothers (Babbu’) have a central role in the lives of Blater, not only as caregivers, but also as sources of morals, spirituality, and blessings in life. Blater view mothers as “bungka” or living talismans whose prayers and blessings determine their safety and success. Non-formal education such as Islamic boarding schools also shape the values of respect for mothers. In addition, the instillation of values by mothers, who tend to be gentle and loving, has a strong influence in shaping the Blater's attitude of respect, in contrast to the masculine values taught by fathers. This research is known to show Blater's rarely published humanist side, and provides a new perspective in viewing the role of mothers in Madurese culture, especially in figures who have long been synonymous with violence, assertiveness and courage.